2008
DOI: 10.3748/wjg.14.3681
|View full text |Cite
|
Sign up to set email alerts
|

Experimental treatment of pancreatic cancer with two novel histone deacetylase inhibitors

Abstract: Our findings suggest that NVP-LBH589 and NVP-LAQ824 are active against human pancreatic cancer, although the precise mechanism of in vivo drug action is not yet completely understood. Therefore, further preclinical and clinical studies for the treatment of pancreatic cancer are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…Recent studies have shown that HDACis have the potential to inhibit carcinogenesis and fibrogenesis (2,(9)(10)(11)(12)(13)(14)(15). VPA, a semiselective HDACi (20), is widely prescribed for patients with epilepsy and psychiatric disorders and well tolerated by the majority of patients (21,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that HDACis have the potential to inhibit carcinogenesis and fibrogenesis (2,(9)(10)(11)(12)(13)(14)(15). VPA, a semiselective HDACi (20), is widely prescribed for patients with epilepsy and psychiatric disorders and well tolerated by the majority of patients (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Histone acetylation and deacetylation is controlled by histone acetyltransferases and histone deacetylases. In recent years, histone deacetylase inhibitors (HDACis) showed anti-cancer activities and are, therefore, of clinical interest (9)(10)(11)(12). There are also several reports showing an antifibrogenic effect of HDACis, but the underlying mechanism is still unclear (2,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Gemcitabine, acting as an antimetabolite, can inhibit ribonucleotide reductase and DNA synthesis, and induce apoptosis [33] . Gemcitabine today remains a first-line drug for patients with advanced pancreatic cancer [7][8][9] . However, it has a narrow therapeutic index due to rapid enzyme deamination by deoxytidine deaminase into its corresponding inactive uracil derivative, and can also induce drug resistance [34,35] .…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine is an active nucleoside analogue against a wide variety of cancers, including nonsmall cell lung cancer and pancreatic cancer [7][8][9] . Gemcitabine, acting as an antimetabolite, can inhibit ribonucleotide reductase and DNA synthesis, and induce apoptosis [33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation